The Impact of Green Cell Construction in Prisons - Esmaeili, Alireza (International Journal of Psychosocial Rehabilitation, 2020)
Green space design in prisons refers to a design in which, by enclosing a part of prison with the approximate area of 400 meters, a green space with natural elements is created such as a cliff, waterfall, pergola, and planting flowers and grass as well as tree and bushes. This Green Cell project is an incentive project and its enclosure makes it inaccessible and this allows prison officials to encourage prisoners to improve their behavior and morals. Prisoners who had good morals and behavior during the week used this opportunity to visit their families in person. The harsh and solid environment of the prison with high cement walls and iron balls increases the value of the green space for the prisoner during the time they spend in the prison and being in such a green environment with a natural space such as waterfall, flower, and grass, encourages the prisoner to live and change their personalities. This environment has had a positive impact not only on the prisoner, but also on their families, their children in particular, as well as officials and prison officers, and had reduced the depression and stress of the prison’s environment and becomes as helping tools for the officials in order to discipline the prisoners. The current plan was implemented in the reform school in Isfahan Prison.